KELURAHAN BINAAN : PROGRAM PEMBERDAYAAN MASYARAKAT DI KELURAHAN TOSA - Lestari, Tutik; Andiani, Andiani; Yusnita, Yusnita; Daud, Ruslia; Aulia, Rifanda; Aldjokdja, Retno Kartika; Sahsun, Darmila; Sumarto, Sabaria; Diman, Tiara; Langasa, Siti AIgina; Bada, Wahdi; Manteto, Tiara; Salim, Nurmai; M, Fitra Tunisyah; F, Fadila S. Hi.; Hasan, Risma Hi; Laego, Riyanti; Minggu, Musdalifa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In an effort to increase public awareness and involvement in the importance of environmental protection, the Faculty of Health Sciences, University of Muhammadiyah North Maluku (FIKes UMMU) initiated the Assisted Village program as a form of community service. This program aims to build synergy between the academic world and the community in creating a healthy, clean, and sustainable environment. Through a participatory approach, FIKes UMMU not only provides education on environmental health but also encourages the community to actively participate in concrete actions to maintain the cleanliness and sustainability of the environment around them. By making the village as a fostered partner, it is hoped that there will be collective behavioral changes that support community-based health development.